Atlantic water variability on the SE Greenland continental shelf and its relationship to SST and bathymetry. Issue 2 (20th February 2013) - Sutherland, David A.; Straneo, Fiammetta; Stenson, Garry B.; Davidson, Fraser J.M.; Hammill, Mike O.; Rosing‐Asvid, Aqqalu
Abstract : [1] Interaction of warm, Atlantic‐origin water (AW) and colder, polar origin water (PW) advecting southward in the East Greenland Current (EGC) influences the heat content of water entering Greenland's outlet glacial fjords. Here we use depth and temperature data derived from deep‐diving seals to map out water mass variability across the continental shelf and to augment existing bathymetric products. We compare depths derived from the seal dives with the IBCAO Version 3 bathymetric database over the shelf and find differences up to 300 m near several large submarine canyons. In the vertical temperature structure, we find two dominant modes: a cold mode, with the typical AW/PW layering observed in the EGC, and a warm mode, where AW is present throughout the water column. The prevalence of these modes varies seasonally and spatially across the continental shelf, implying distinct AW pathways. In addition, we find that satellite sea surface temperatures (SST) correlate significantly with temperatures in the upper 50 m ( R = 0.54), but this correlation decreases with depth ( R = 0.22 at 200 m), and becomes insignificant below 250 m. Thus, care must be taken in using SST as a proxy for heat content, as AW mainly resides in these deeper layers. Sample Unit Level Copyright Key Points: New dataset identifies 2 modes of temperature variability on SE Greenland shelf Prevalence of Atlantic‐origin waters depends on season and shelf location SST cannot be used as a proxy for water temperatures >250 m deep